Deixis Found in “Good Neighbors-Spongebob Squarepants” Transcription : A Pragmatics Analysis - Herningtyasari, Gadis; Himawati, Ulya; Talenta, Pratama Irwin (English Language and Education Spectrum, 2024)
This research is to analyze deixis in the movie of Good Neighbors of a SpongeBob SquarePants episode from season four . SpongeBob Square Pants (often referred to simply as SpongeBob) is an American animated television series, created by marine biologist and animator Stephen Hillenburg. Whereas deixis is one of the most important notions in general linguistics and is a vital link between the real-life environment around us such as time frame, physical location, people involved, etc and what we actually say the linguistic terms used. The result describes the kinds of deixis and the referents of deixis in Good Neighbor-SpongeBob Squarepants Transcription which finds many referents that show different kinds of deixis. Finally, From the analysis, it is found that the Pronoun Deixis is often used. In almost all conversation the personal pronoun "you" existed. Its pronoun almost refers to the spongebob and squidward. The other personal pronoun was "we" that refers to spongbob and patrick. Besides, the possessive pronoun "our" has the same interpretation. File pronoun of "I"is used. "I" refers to the actor. The actors are SpongeBob, squidward, patrick and etc. Finally, it is many deixis that is used in Good Neighbor of SpongeBob Squarpants. Thus, many deixises that is found in this transcript.